ANALYTICAL APPROACH TO THE DIRECT COLLISIONS PROBLEM IN ACTIVE GALAXY NUCLEUS - Omarov, Ch. T. (Recent Contributions to Physics, 2009)
A model of N- bodies stellar system with physical collisions of its components is considered in this paper.